The 'diagonal' approach to Global Fund financing: a cure for the broader malaise of health systems? - Baker Brook K; Van Damme Wim; Ooms Gorik; Zeitz Paul; Schrecker Ted (BMC, 2008)
Abstract Background The potentially destructive polarisation between 'vertical' financing (aiming for disease-specific results) and 'horizontal' financing (aiming for improved health systems) of health services in developing countries has found its way to the pages of Foreign Affairs and the Financial Times. The opportunity offered by 'diagonal' financing (aiming for disease-specific results through improved health systems) seems to be obscured in this polarisation. In April 2007, the board of the Global Fund to fight AIDS, Tuberculosis and Malaria agreed to consider comprehensive country health programmes for financing. The new International Health Partnership Plus, launched in September 2007, will help low-income countries to develop such programmes. The combination could lead the Global Fund to fight AIDS, Tuberculosis and Malaria to a much broader financing scope. Discussion This evolution might be critical for the future of AIDS treatment in low-income countries, yet it is proposed at a time when the Global Fund to fight AIDS, Tuberculosis and Malaria is starved for resources. It might be unable to meet the needs of much broader and more expensive proposals. Furthermore, it might lose some of its exceptional features in the process: its aim for international sustainability, rather than in-country sustainability, and its capacity to circumvent spending restrictions imposed by the International Monetary Fund. Summary The authors believe that a transformation of the Global Fund to fight AIDS, Tuberculosis and Malaria into a Global Health Fund is feasible, but only if accompanied by a substantial increase of donor commitments to the Global Fund. The transformation of the Global Fund into a 'diagonal' and ultimately perhaps 'horizontal' financing approach should happen gradually and carefully, and be accompanied by measures to safeguard its exceptional features.